Genetic Approaches to Assessing Evidence for a T Helper Type 1 Cytokine Defect in Adult Asthma - Birkisson, Illugi F; Halapi, Eva; Bjornsdottir, Unnur S; Shkolny, Dana L; Adalsteinsdottir, Elva; Arnason, Thor; Gislason, David; Gislason, Thorarinn; Gulcher, Jeffrey; Stefansson, Kari; Hakonarson, Hakon (American journal of respiratory and critical care medicine, 2004)
Recent evidence suggests that deficiency in the Th1 cytokine pathway may underlie the susceptibility to allergic asthma. This study examined whether (1) single-nucleotide polymorphisms exist in the promoter region of the two interleukin (IL)-12 subunit genes in patients with asthma; (2) messenger RNA and protein expressions of signal transducers and activators of transcription, IL-12, IFN-gamma, and their receptors are altered in asthma; and (3) linkage to genes in the Th1 pathway is present in families with asthma in Iceland. The promoter regions of the IL-12 subunit genes were sequenced in 94 patients with asthma and 94 control subjects without asthma. Linkage was examined in 169 families that included over 570 patients with asthma and 950 of their unaffected relatives. The results demonstrate no evidence of linkage to microsatellite markers in close association with genes within the Th1 pathway, and no polymorphism was detected in the promoter regions of the two IL-12 subunit genes in the cohort with asthma patients. Moreover, we found no differences in the messenger RNA or protein expression signals of genes in the IL-12 pathway between the patients and control subjects. We conclude that decrease in Th1 type cytokine response is unlikely to present a primary event in asthma.